2021
DOI: 10.3329/aba.v24i2.55781
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Year Spatiotemporal Change Record of Sundarban Mangrove Forest in Bangladesh

Abstract: Accurate and realistic forest cover change assessment is essential for the conservation and management of the Sundarban mangrove forest of Bangladesh. With these views, an integrated way of the vegetation cover assessment was conducted using time-series Landsat satellite imageries of 1991, 2001, 2011, and 2021. During the last 30-year (1991-2021), variations in four land cover classes viz. healthy vegetation, unhealthy vegetation, water body, and sandbar were recorded. It showed a decreasing trend of forest ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Given Bangladesh's heavy reliance on agriculture and vulnerability to climate change, it presents an intriguing case study for investigating water and vegetation cover changes using multispectral satellite images. In a separate investigation, Uzzaman et al (2020) utilized multispectral Landsat satellite imageries of 1991, 2001, 2011, and 2021 to identify transformations in water bodies and vegetation cover within the Sundarbans, an expansive mangrove forest in southwestern Bangladesh. The study revealed a decreasing trend of forest vegetation and a subsequent increase of water bodies during the study period, attributed to a combination of anthropogenic factors like deforestation, coastal accretion, and erosion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given Bangladesh's heavy reliance on agriculture and vulnerability to climate change, it presents an intriguing case study for investigating water and vegetation cover changes using multispectral satellite images. In a separate investigation, Uzzaman et al (2020) utilized multispectral Landsat satellite imageries of 1991, 2001, 2011, and 2021 to identify transformations in water bodies and vegetation cover within the Sundarbans, an expansive mangrove forest in southwestern Bangladesh. The study revealed a decreasing trend of forest vegetation and a subsequent increase of water bodies during the study period, attributed to a combination of anthropogenic factors like deforestation, coastal accretion, and erosion.…”
Section: Literature Reviewmentioning
confidence: 99%